Association of smoking and right ventricular function in middle age: CARDIA study. Issue 1 (8th March 2020) - Moreira, Henrique T; Armstrong, Anderson C; Nwabuo, Chike C; Vasconcellos, Henrique D; Schmidt, Andre; Sharma, Ravi K; Ambale-Venkatesh, Bharath; Ostovaneh, Mohammad R; Kiefe, Catarina I; Lewis, Cora E; Schreiner, Pamela J; Sidney, Stephen; et al.
Abstract : Objective: To evaluate the association of cigarette smoking and right ventricular (RV) systolic and diastolic functions in a population-based cohort of individuals at middle age. Methods: This cross-sectional study included participants who answered the smoking questionnaire and underwent echocardiography at the Coronary Artery Risk Development in Young Adulthood year 25 examination. RV systolic function was assessed by echocardiographic-derived tricuspid annular plane systolic excursion (TAPSE) and by right ventricular peak systolic velocity (RVS'), while RV diastolic function was evaluated by early right ventricular tissue velocity (RVE'). Multivariable linear regression models assessed the relationship of smoking with RV function, adjusting for age, sex, race, body mass index, systolic blood pressure, total cholesterol, high-density lipoprotein (HDL) cholesterol, diabetes mellitus, alcohol consumption, pulmonary function, left ventricular systolic and diastolic function and coronary artery calcium score. Results: A total of 3424 participants were included. The mean age was 50±4 years; 57% were female; and 53% were black. There were 2106 (61%) never smokers, 750 (22%) former smokers and 589 (17%) current smokers. In the multivariable analysis, current smokers had significantly lower TAPSE (β=−0.082, SE=0.031, p=0.008), RVS' (β=−0.343, SE=0.156, p=0.028) and RVE' (β=−0.715, SE=0.195, p<0.001) compared with never smokers. Former smokers had a significantly lower RVE' compared with never smokers (β=−0.414, SE=0.162, p=0.011), whereas no significant difference in RV systolic function was found between former smokers and never smokers. Conclusions: In a large multicenter community-based biracial cohort of middle-aged individuals, smoking was independently related to both worse RV systolic and diastolic functions.